The Smart Wheelchair / Nik Afiqah N. Ahmad Yani - N. Ahmad Yani, Nik Afiqah; Zaimy, Nur A’fyah; Rozali, Muhammad Amirul Aiman; Zakaria, Nur Aqilah; Razif, Siti Nurhawani (2022)
Technology plays an important role in human life nowadays. Technology is used to solve human problems and, with the advent of technology, it can help to give humans a better quality of life. Since the concept of the technology itself is to solve real-world problems, then, there is our company, The Catalyst coming out with an innovation of Internet of Things technology, namely the Smart Wheelchair. This technology of Smart Wheelchair aims to help the elderly with wheelchairs by detecting the occurrence of a fall, then sending a notification alert to the caregivers. The Smart Wheelchair is a new product developed to the world, where it will lead to a new market, satisfying the need of the consumers if properly developed, and will reach the international market if marketed strategically. By surveying the targeted customer, the arising issue regarding this product of Smart Wheelchair is addressed. As well, Consumer Trends Canvas or also known as CTC is being implemented to help the company understand any consumer trend. By completing CTC analysis, the company can gather and analyse insights regarding consumer trends and transform them into an innovation, which opens to a business opportunity. During the new product development process, there are five different tasks have been performed before introducing the products to the consumer. The task accomplished includes the research and development, designing the product, conducting concept testing, making the prototype and lastly conducting a test marketing. The 5 processes carried out during new product development are further explained in one of the sections in this report.